MSC-Derived Extracellular Vesicles: Roles and Molecular Mechanisms for Tissue Repair - Wu T; Liu Y; Wang S; Shi C (International Journal of Nanomedicine)
Tingting Wu,1,2,* Yajing Liu,1,2,* Shuman Wang,1,2 Chen Shi1– 3 1Department of Pharmacy, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2Hubei Province Clinical Research Center for Precision Medicine for Critical Illness, Wuhan, Hubei, People’s Republic of China; 3Hubei Key Laboratory of Natural Active Polysaccharides, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chen Shi, Email whxhchen@163.comAbstract: Mesenchymal stem cells (MSCs) are pluripotent stem cells that have great potential in the field of regenerative medicine. Extracellular vesicles that derived from MSCs inherit the bioactive molecules, including lipids, proteins, nucleic acids, from the donate cells. With similar biological functions as MSCs, MSC-EVs show lower toxicity, better biocompatibility, stability, and less immune rejection. Therefore, MSC-EVs are emerging as a cell-free alternative therapy for MSC-based cell therapy. Here, we reviewed the characteristics of different subtype of MSC-EVs, the functional molecules in MSC-EVs for tissue repair, the potential applications of MSC-EVs for different tissue injuries in recent three years, and the clinical progress as well as the existing challenges in MSC-EV based therapy. This review would provide some insights for the future researches and clinical translation of MSC-EVs in regenerative medicine. Keywords: mesenchymal stem cells, extracellular vesicles, cell-free therapy, tissue repair, regenerative medicine